International Monetary Fund Annual Report 1950. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 1950)
This paper reviews key findings of the IMF's Annual Report for the fiscal year ended April 1950. The report highlights that the widespread devaluation of currencies that took place in September 1949 was the most far-reaching in any comparable period in recent times. Thirteen members agreed new par values with the IMF, most of them involving a devaluation of approximately 30.5 percent in relation to the U.S. dollar. Six member countries with which the IMF has no agreed par value also depreciated their exchange rates.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet